PERBANDINGAN PEMAKAIAN ROCKER ARM KONVENSIONAL DENGAN ROCKER ARM ROLLER BEARING PADA SEPEDA MOTOR - Jusnita (Jurnal Surya Teknika, 2021)
Roller Rocker Arm is important for transmitting signals and determining work efficiency which is the result of technological developments from ordinary rocker arms. The purpose of this study was to compare the use of conventional rocker arm with rocker arm roller on power, torque, exhaust emissions, compression on a motorcycle engine. The research method used is changing the fuel system, ignition system, changing the valve mechanism. The maximum torque on the conventional rocker arm occurs at 2995 rpm with a value of 10.92 Nm. Maximum torque decreases with increasing engine speed. The decrease in power at high speed occurs due to the influence of the volume of the fuel and air mixture which tends to decrease. The highest fuel consumption occurs at 7000 rpm engine speed in a conventional rocker arm of 0.124 kg/kWh, so the rocker arm roller is more efficient than the conventional rocker arm. Fuel consumption rocker arm roller rotation 7000 rpm 0.028 kg/kWh. While the conventional rocker arm fuel consumption at 7000 rpm 0.124 kg/kWh. Exhaust emissions, the rocker arm roller is environmentally friendly compared to the conventional rocker arm CO2 rocker arm roller only produces 5.2%, while the conventional rocker arm test results after the average CO2 value reaches 5.3%. The results of testing the two rocker arms on compression are the same at 90 Psi and 6.2kg/ from the standard size of 10-11kg/